The technologies on the process of the nurse work - a literature review - Tatiana Rocha; Ana Lucia Abrahão (Universidade Federal Fluminense, Escola de Enfermagem Aurora de Afonso Costa, 2008)
It is a bibliographic review about the concept of technologies on the process of the nurse work on the academic literature. The objective was to identifie articles published between 1994 a 2007 and the identification of the use of " technology" on the work of this professional. The search was done over a indexed data base on the following key words: technology, nurse and work. Were selected 30 articles from them we chose 10 that were relevant to our purpouse. This articles showed a diversity of concepts that the expression technologies is been used, as well considerations over its utilisation.